THE CORRELATION BETWEEN ENDOMETRIOSIS PAIN, MENTAL HEALTH DISORDERS, AND QUALITY OF LIFE IMPACT - Marta Zgierska,; Natalia Pacocha,; Jakub Jędrychowski,; Justyna Popczyńska,; Natalia Karpowicz,; Małgorzata Krzyżanowska,; Julia Kaszucka,; Agnieszka Raczyńska,; Kinga Kosiec,; Oliwia Krzemień, (International Journal of Innovative Technologies in Social Science, 2024)
Introduction: Endometriosis ranks among the prevalent gynecological conditions, impacting approximately 10% of women during their reproductive years. Primarily characterized by pain, endometriosis is also associated with several psychiatric comorbidities such as anxiety, depression and eating disorders. Research also demonstrates a significant decline in the quality of life among patients.The objective of this study is to undertake an exhaustive literature review on endometriosis in women, with a specific focus on understanding its effects on mental health and quality of life.Material and methods: We conducted a literature review utilizing the resources available in the "PubMed" database. The search was performed using following keywords: endometriosis; pelvic pain; anxiety; depression; mental health; eating disorders.Discussion: Research indicates that women diagnosed with endometriosis, particularly those experiencing pain, exhibit elevated stress levels and a diminished quality of life compared to women without the condition. Importantly, depression and anxiety are more prevalent in women with endometriosis, and the presence of psychiatric disorders correlates more to the severity of the endometriosis-related pain than to other disease characteristics. In terms of treatment implications, clinical trials have shown that both medical and surgical interventions for endometriosis not only alleviate physical symptoms but also improve perceived stress, anxiety, and depressive symptoms.Conclusions: We found that severe endometriosis-related pain and the presence of psychiatric disorders were linked to reduced quality of life. Ensuring holistic care for endometriosis is essential for enhancing patients' quality of life. Furthermore, effectively treating endometriosis can alleviate the psychological strain it imposes.